Assessment of COVID-19 vaccine hesitancy among the pregnant women: a mixed-method study from field practice area of Sagar, Madhya Pradesh - Jain, Shefali; Gupta, Amarnath; Dwivedi, Shatkratu; Mishra, Shraddha (International Journal Of Community Medicine And Public Health, 2024)
Background: The World Health Organization defines vaccine hesitancy as a “delay in acceptance or refusal of safe vaccines despite availability of vaccine services”. While pregnancy does not inherently increase susceptibility to COVID-19, pregnant women face higher risks of severe illness if infected. Misconceptions during the crucial antenatal care period contribute to vaccine hesitancy. This study aimed to assess COVID-19 vaccine hesitancy among pregnant women in Sagar, Madhya Pradesh. Methods: A mixed-method study was conducted using multistage random sampling. The study involved 70 unvaccinated pregnant women from the field practice area of Polyclinic Chameli Chowk and in-depth interviews with 17 key informants, including district immunization officers, vaccination officers, and health care workers. Inclusion criteria were unvaccinated pregnant women under 50 years, willing to participate, and without contraindications for COVID-19 vaccination. Data collection tools included a pre-tested semi-structured questionnaire for quantitative data and a question guide for qualitative data. Results: Among the 70 unvaccinated pregnant women, 49 (70%) were primigravida, and 21 (30%) were multigravida. A significant majority, 57 (81.3%), were unemployed (housewives). Vaccine hesitancy was identified in 66 (94.2%) women, while 4 (5.7%) were resistant to vaccination. Conclusions: The study highlights the importance of communication from trusted sources, easy access to vaccines, and community engagement in addressing vaccine hesitancy among pregnant women. The findings suggest targeted interventions to reduce hesitancy and ensure timely mass immunization against COVID-19.